2017
DOI: 10.1111/mcn.12475
|View full text |Cite
|
Sign up to set email alerts
|

Higher maternal vitamin D concentrations are associated with longer leukocyte telomeres in newborns

Abstract: Gestational vitamin D insufficiency is related with increased risks of various diseases and poor health outcomes later in life. Telomere length at birth or early in life is known to be a predictor of individual health. Both vitamin D and telomere length are related with various health conditions, and vitamin D concentrations are associated with leukocyte telomere lengths in women.We investigated the association between maternal vitamin D concentrations and newborn leukocyte telomere lengths. This cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 68 publications
3
29
0
Order By: Relevance
“…Telomeres may also be susceptible to poor or unbalanced nutrition ( 21 ). Prepregnancy BMI has been found to be inversely associated with newborn TL ( 22 ), whereas maternal folate ( 7 , 23 ), vitamin C ( 24 ), and vitamin D ( 25 ) have been associated with longer telomeres in newborns. The aim of the present study was to assess the potential impact of multiple markers of maternal nutritional status on TL in placenta and cord blood.…”
Section: Introductionmentioning
confidence: 99%
“…Telomeres may also be susceptible to poor or unbalanced nutrition ( 21 ). Prepregnancy BMI has been found to be inversely associated with newborn TL ( 22 ), whereas maternal folate ( 7 , 23 ), vitamin C ( 24 ), and vitamin D ( 25 ) have been associated with longer telomeres in newborns. The aim of the present study was to assess the potential impact of multiple markers of maternal nutritional status on TL in placenta and cord blood.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent study reported an association between cord blood levels of dehydroepiandrosterone sulfate (DHEAS), reactive oxygen species and newborn LTL [ 192 ]. Finally, yet other studies have reported associations between maternal oestrogen levels [ 193 ], folate [ 166 ] and vitamin D status during pregnancy [ 194 ] with newborn LTL.…”
Section: Fetal Programming Of the Telomere Biology Systemmentioning
confidence: 99%
“…Second, maternal vitamin D concentration was examined for associations with LTL in newborn cord blood samples in a model adjusted for the maternal age, BMI, LTL, white blood cell count, glycosylated haemoglobin level, health behaviours (smoking, exercise, body weight before pregnancy, medical history) and nutritional intake and for the newborn's sex and birthweight. The study concluded that maternal vitamin D levels were also positively associated with newborn LTL [99].…”
Section: Vitaminsmentioning
confidence: 91%
“…TL in children can be affected by oxidative, immune, endocrine and metabolic pathways in a way that accelerates cellular dysfunction over the lifespan [11,92], thus reflecting the effect of specific conditions on the later susceptibility to a disease. Maternal stress [93][94][95], hormones [96], smoking [97], race [98], vitamin concentrations [99,100], pre-pregnancy body mass index (BMI) [101] and other factors showed correlation with TL and pointed out the importance of in utero exposures in the regulation of newborn TL. In this section we will focus on some of the most pertinent antenatal determinants.…”
Section: Determinants Of Newborn Tlmentioning
confidence: 99%